Photocatalytic Degradation of Synthetic Dye Wastewater Using Photocatalysts Modified with Coffee Ground-Derived Carbon: doi: 10.14456/mijet.2022.21 - Montreepila, Tanawat; Kemacheevakul, Patiya; Chuangchote, Surawut (Engineering Access, 2022)
Textile industries discharge large amounts of colored wastewater which is one of the main environmental problems. It affects aquatic ecosystems and the vision of public water resources. Various processes have been developed for the degradation of dye wastewater, one of the most attractive and promising alternative technologies is semiconductor photocatalysis because the reactions can occur at room temperature and pressure. Several studies on photocatalysts, zinc oxide (ZnO) nanoparticles are promising photocatalysts with high photocatalytic activity, biocompatibility, and nontoxicity to human cells. One of the techniques used to enhance the properties of ZnO is doping, especially with carbon (C). Doping the crystal lattice of ZnO with C allows a shift of the bandgap from the UV to the visible light. C can be synthesized from various kinds of waste. Coffee ground waste is one of the interesting C sources. Therefore, it is a good solution to convert coffee ground waste to a C source. In this research, C-doped ZnO was synthesized by a hydrothermal process for the degradation of synthetic dye wastewater (methylene blue). ZnO was modified with C solution (i.e. 10 mL, 20 mL, and 30 mL). The result indicated that the photocatalytic effect of the composites showed a phenomenon of first strengthening and then weakening. The highest photocatalytic degradation was obtained on the C-doped ZnO with an initial C solution of 20 mL. The removal efficiency of color was 91% under visible light.